Monitoring of functional fitness of combat athletes during the precompetitive preparation stage - Pryimakov, Oleksandr; Iermakov, Sergii; Kolenkov, Oleksandr; Samokish, Ivan; Juchno, Jury (My University, 2016)
Objective. The objective of the work consisted in substantiating criteria and elaborating differential estimates of functional fitness of highly skilled wrestlers at precompetitive stage of preparation. Material and methods. From 12 to 54 athletes aged 20-28 years, members of the national teams of Ukraine in Greco-Roman and free-style wrestling, and judo participated in studies. Functional fitness and special work capacity of wrestlers were estimated on the basis of the methods of electrocardiography, variation pulsography, pulsometry, gas analysis, physical work capacity testing. Results. The major criteria of wrestlers’ functional fitness at rest and in body responses to physical load appeared to be: 1) cardiac function bradycardia and low index of myocardial tension under basal conditions in prone position; 2) high reactivity of cardiovascular system during physical load; 3) economy of physiological system functioning, low tension in regulatory system activity; 4) high level of speed capacities and functional stability of the body of wrestlers during specialized physical loads. The key integrative indices of wrestlers’ fitness general structure appeared to be: special work capacity level, general level of functional fitness, mobility of physiological processes, economy, anaerobic power. Developed mathematical models reflect different variants of interrelations and ratios of the key and integral physiological indices with respect to skill level, weight category and the level of athletes’ special work capacity. Formalization of these dependences provides more efficient approach to the issue of controlling, modelling and managing functional fitness and special work capacity of wrestlers at the stage of maximal realization of individual capacities. Conclusions. Increase of specific weight of the key integrative functional indices in special work capacity determination along with the enhancement of wrestlers’ skill level represents the most significant criterion for improvement of their fitness structure.
Pryimakov O. Monitoring of functional fitness of combat athletes during the precompetitive preparation stage / O. Pryimakov, S. Iermakov, O. Kolenkov, I. Samokish, J. Juchno // Journal of Physical Education and Sport (JPES), 2016. - V.16, Issue 2, Art 87. - P. 551-561.
Keywords: wrestlers; functional fitness; weight categories; skill level; models